Exploring lifespan development - Berk, Laura E. (Boston : Pearson, 2008)
Contenido: Theory and research in human development. History, theory and research strategies. Foundations of development. Biological and environmental foundations. Infancy and toddlerhood: the first two years. Physical development in infancy and toddlerhood. Cognitive development in infancy and toddlerhood. Emotional and social development in infancy and toddlerhood. Early childhood: two to six years. Physical and cognitive development in early childhood. Middle childhood: six to eleven years. Adolescence: the transition to adulthood. Early adulthood. Middle adulthood. Late adulthood. The end of life.